Learning From Agility, Partnership and Innovation During the Covid-19 Pandemic: A Perspective From Industry - Cárdenas, Ana María; Roger-Dalbert, Celine (Frontiers in Cellular and Infection Microbiology, 2022)
Two years after the COVID-19 pandemic started, the world continues to adapt to the profound effects that Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has had on our lives. As the global crisis took hold, many looked to the medical technology/device industry for guidance and solutions. All while the industry itself, was disrupting its own processes and activities. In order to evolve and deliver accelerated innovation the industry had to be agile, resilient and collaborative with the broader healthcare community and technology partners. Now comes a time when we will start to see what changes were temporary and which ones will become part of the new process, but one thing is certain, we will not be going back to where we were pre-pandemic.